Assessment of gold mine tailings as partial sand substitute in nonloadbearing concrete hollow blocks - Germar, Anne Victoria B.; Pagapong, Kim Lloyd C.; Junio, Jessica M. (Quezon City College of Engineering, University of the Philippines Diliman, 2018)
Mine tailings are one of the by-products of mining activities. The tailings retain the heavy metal-containing chemicals that were used in the process of extraction (e.g. amalgamation), resulting to these wastes becoming hazardous. The most common disposal method for these mining wastes are by storing them indefinitely in tailing dams, but these dams are expensive to maintain, occupy large areas and are prone to leakage and collapse. Using cement solidification/stabilization (S/S) as the immobilization method, the study aims to utilize mine tailings as a partial substitute to sand in the production of nonloadbearing concrete hollow blocks, which can potentially be a viable disposal method given the recent construction boom in the country. After obtaining the physical, chemical, and mineralogical characteristics of the mine tailings, the samples were produced with varying replacement levels of gold mine tailings, replacement levels used were 0%, 10%, 15%, 20% and 25% by weight and with a ratio of mixing water-to-cement-to-aggregate of 1:1:7. A total of 40 samples were produced and samples were cured for 14 days and 28 days. All samples for both curing times were determined to have a compressive strength greater than 500 psi, exceeding the minimum compressive strength requirement stated in ASTM C129. To obtain the leachate from the samples. two leaching procedures were performed, namely the Toxicity Characteristic Leaching Procedure (TCLP) and Synthetic Precipitation Leaching Procedure (SPLP) method. The leachate was analyzed for toxicity using Inductively Coupled Plasma Optical Emission Spectroscopy (ICP-OES) and it was determined that Arsenic, Copper, Lead, and Cadmium were all successfully immobilized. However, cement S/S was not successful in immobilizing Mercury. Due to the high concentration of Mercury in the gold mine tailings sample, its utilization in concrete hollow blocks require further treatment using other methods that could immobilize Mercury.
Thesis (Bachelor of Science in Civil Engineering)--University of the Philippines Diliman
Keywords: Tailings (Metallurgy); Concrete blocks; Waste products as building materials